2010
DOI: 10.1111/j.1574-6941.2010.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling and identification of methanogenic archaeal species from rabbit caecum

Abstract: During a comparison of 16S rDNA PCR-denaturant gradient gel electrophoresis (DGGE) profiles of methanogenic archaea from rumen fluid, rabbit caecum and pig feces, a unique band common to all rabbit caecum samples was observed. DGGE profiling also showed that the methanogen community from the New Zealand White adult rabbits is different and less complex than the methanogen communities from the rumen and pig feces. Small subunit ribosomal gene sequences of methanogenic archaea were subsequently retrieved from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 40 publications
(51 reference statements)
1
24
1
2
Order By: Relevance
“…The following archaea were abundantly distributed in all the twelve libraries: Methanobrevibacter , Methanosphaera and unclassified Euryarchaeota. Therefore, we suggested that the methanogenic community in rabbit caecum is unique and of low complexity with few dominating species, which is in agreement with the findings of a previous report (Kušar and Avguštin, ). Polysaccharides such as cellulose, hemicellulose, pectin and starch are widely present in plants.…”
Section: Resultssupporting
confidence: 92%
“…The following archaea were abundantly distributed in all the twelve libraries: Methanobrevibacter , Methanosphaera and unclassified Euryarchaeota. Therefore, we suggested that the methanogenic community in rabbit caecum is unique and of low complexity with few dominating species, which is in agreement with the findings of a previous report (Kušar and Avguštin, ). Polysaccharides such as cellulose, hemicellulose, pectin and starch are widely present in plants.…”
Section: Resultssupporting
confidence: 92%
“…The simplicity of the capillary electrophoresis single-strand conformation polymorphism (CE-SSCP) profiles obtained for the archaeal community ( Figure 2c) indicates much lower species diversity than the bacterial population (Figure 2a). The molecular inventory of the archaeal population (Kušar and Avguštin, 2010) confirmed the predominance of the genus Methanobrevibacter and suggested the presence of a new species specific to rabbit.…”
Section: Specific Diversity Of the Rabbit Gut Ecosystemmentioning
confidence: 76%
“…Contrary in rabbit, this community is not so well studied. Recently, Kušar and Avguštin () studied the molecular profile of methanogenic archaeal species from rabbit caecum and reported that it is inhabited by members of the genus Methanobrevibacter and possibly one‐species dominated, which seem to belong to distinct phylogenetic group containing Methanobrevibacter woesei, Methanobrevibacter thaueri and Methanobrevibacter gottschalkii . Regardless the different community structure observed in caecum and rumen, the number of species (richness) was similar.…”
Section: Discussionmentioning
confidence: 99%
“…() recently observed that the archaeal community in soft and hard faeces of rabbits differed form that in the rumen of cows. Kušar and Avguštin () reported that the rabbit′s caecum harbours methanogenic community that is unique and exerts low complexity with few dominant species. However, comparative data integrating diversity, microbial biomass and fermentation pattern in rumen and caecum are still lacking.…”
Section: Introductionmentioning
confidence: 99%